Analysis of the dynamics of the decay D + → K S 0 π 0 e + ν e - Ablikim, M; Achasov, MN; Adlarson, P; Afedulidis, O; Ai, XC; Aliberti, R; Amoroso, A; An, Q; Bai, Y; Bakina, O; Balossino, I; Ban, Y; et al. (Springer, 2024)
The branching fraction of D+→KS0π0e+νe is measured for the first time using 7.93 fb−1 of e+e− annihilation data collected at the center-of-mass energy s = 3.773 GeV with the BESIII detector operating at the BEPCII collider, and is determined to be BD+→KS0π0e+νe=0.881±0.017stat.±0.016syst.%. Based on an analysis of the D+→KS0π0e+νe decay dynamics, we observe the S-wave and P-wave components with fractions of fS-wave = (6.13 ± 0.27stat.± 0.30syst.)% and fK¯∗8920=93.88±0.27stat.±0.29syst.%, respectively. From these results, we obtain the branching fractions BD+→KS0π0S−wavee+νe=5.41±0.35stat.±0.37syst.×10−4 and BD+→K¯∗8920e+νe=4.97±0.11stat.±0.12syst.%. In addition, the hadronic form-factor ratios of D+→K¯∗8920e+νe at q2 = 0, assuming a single-pole dominance parameterization, are determined to be rV=V0A10=1.43±0.07stat.±0.03syst. and r2=A20A10=0.72±0.06stat.±0.02syst..